Survey analysis and data management in the Caribbean - St. Bernard, Godfrey ([CCMS] [St. Augustine]TT, 2001)
Highlights some of the critical factors that may have been responsible for limiting efforts to establish a framework to build multipurpose databases within the Anglophone Caribbean.